Digging deep: Resource exploitation and higher education - Lenin H. Balza; Camilo de los Rios Rueda; Nathaly M. Rivera (Inter-American Development Bank (IDB), 2022)
Do resource-extraction booms crowd out postsecondary education? We explore this question by examining the higher education-related decisions of Chilean high school graduates during the 2000s commodities boom. We find mineral extraction increases a person's likelihood of enrolling in postsecondary technical education while reducing the likelihood of completing a four-year professional degree program. Importantly, effects are heterogeneous across economic backgrounds. The impact on college dropouts is primarily present among students that graduated from public high schools, which generally cater to low-income groups. Our findings show that natural resources may affect human capital accumulation differently across income groups in resource-rich economies.
Keywords: Q32; Q33; I23; I25; I26; 330; Extractive Industries; Natural Resources; Resource Curse; ResourceBooms; Human Capital; Education; Latin America; Chile